Femoral neck system versus dynamic hip screw for fixation of femoral neck fracture in the adult: a meta-analysis - Qi Long Jiang,; Yong Cao,; Xinwen Bai,; Yu Deng,; Li, Yan (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the efficacy of femoral neck system compared to dynamic hip screws in treating femoral neck fractures. Method: The systematic review was conducted from January to March 2023, and comprised literature search on PubMed, Embase, Scopus, Ovid, Cochrane Central Register of Controlled Trials, China National Knowledge Infrastructure and Wanfang databases for relevant studies published up to March 1, 2023. Study data as well as demographic and outcome parameters related to the patients were extracted, and the methodological index for non-randomised studies was used to assess the risk of bias. Review Manager software was used to conduct meta-analysis. Results: Of the 567 studies initially found, 6(1%) were included, with the publication date ranging from August 2021 to February 2023. There were 5(83.3%) studies published in English and 1(16.7%) in Chinese. Of the 577 patients with femoral neck fractures, 287(49.7%) were treated with femoral neck system and 290(50.3%) with dynamic hip screws. Significant differences were shown between the two groups regarding operation duration, blood loss, internal fixation failure rate and Harris hip score (p=<0.05). There was no significant differences between the groups regarding time from injury to surgery, hospitalisation, complication rate and femoral neck shortening rate (p>0.05). Conclusion: The novel femoral neck system could optimise surgical procedures, with shorter operation times and lesser blood loss. The femoral neck system and dynamic hip screws were comparable in terms of complication rates and postoperative hip function. Key Words: Femoral neck fractures, Internal fixators, Meta-analysis.